HUBUNGAN ANTARA SUPERVISI KLINIS DAN DISIPLIN KERJA DENGAN KOMPETENSI GURU DI UPTD SDN KECAMATAN GUNUNGSITOLI - Fitriani Waruwu; Efendi Napitupulu; Maximus Gorky Sembiring; Syahril . (Jurnal Teknologi Pendidikan (JTP), 2024)
Abstract: The improvement of teacher competence in the UPTD SDN district of Gunungsitoli aims to enhance Indonesia's competitiveness and to promote the intellectual development of the nation. The competencies possessed by teachers enable them to manage the learning process in fostering students' interest and participation. This research aims to determine the relationship between clinical supervision and work discipline with teacher competence in the UPTD SDN district of Gunungsitoli. The research population consists of teachers in the UPTD SDN district of Gunungsitoli. The sampling technique used in this study is proportional random sampling, with a total sample size of 206 individuals. Data collection was done using questionnaire techniques. The instrument has been tested and proven to be valid and reliable. The data were analyzed using descriptive statistical analysis and pearson product moment correlation coefficient formula. The research results indicate that there is a correlation between clinical supervision and teacher competence in the UPTD SDN district of Gunungsitoli, a correlation between work discipline and teacher competence in the UPTD SDN district of Gunungsitoli, and a correlation between clinical supervision, work discipline, and teacher competence in the UPTD SDN district of Gunungsitoli.   Keywords: Clinical Supervision, Work Discipline, and Teacher Competence  Abstrak: Peningkatan kompetensi guru di UPTD SDN kecamatan Gunungsitoli bertujuan untuk mewujudkan daya saing Indonesia serta dalam rangka mencerdaskan kehidupan berbangsa dan bernegara. Kompetensi yang dimiliki oleh guru memampukan guru memanajemen proses pembelajaran dalam menumbuhkan minat dan partisipasi peserta didik. Penelitian ini bertujuan untuk mengetahui hubungan supervisi klinis dan disiplin kerja dengan kompetensi guru di UPTD SDN kecamatan Gunungsitoli. Penelitian ini menggunakan metode penelitian kuantitatif korelasional. Populasi penelitian adalah guru di UPTD SDN kecamatan Gunungsitoli. Teknik pengambilan sampel menggunakan proporsional random sampling, dengan jumlah sampel sebanyak 206 orang. Teknik pengumpulan data menggunakan teknik pemberian angket. Instrumen telah diuji coba dan dinyatakan valid dan reliabel. Data dianalisis dengan analisis statistik inferensial dan uji korelasi product moment. Hasil penelitian menunjukkan terdapat hubungan supervisi klinis dengan kompetensi guru di UPTD SDN kecamatan Gunungsitoli, terdapat hubungan disiplin kerja dengan kompetensi guru di UPTD SDN kecamatan Gunungsitoli dan terdapat hubungan supervisi klinis dan disiplin kerja dengan kompetensi guru di UPTD SDN kecamatan Gunungsitoli.  Kata Kunci: Supervisi Klinis, Disiplin Kerja dan Kompetensi Guru